Un cine geológico: Tiempos y estética fósiles en el documental Río Turbio (2020) de Tatiana Mazú González - Gattás Vargas, Maia (2023)
This article examines Río Turbio (2020) by Tatiana Mazú González, a documentary that depicts a Patagonian mining town that is the site of political, ecological and feminist conflicts. Using an ecofeminist perspective, as well as notions of the geology of media and deep time, it considers the relationship of the mineral world with the machines and technologies that surround us. It thus finds connections between cinema and geology, and observes how in this film, the times and aesthetics of fossils are translated into a montage of the various visual and sound archives used.